Reversible boric ester-carbene adhesive films - Lai, Wan Jun (Nanyang Technological University, 2023)
The growing interest in the development of tissue adhesives as an alternative to surgical sutures for wound closure can be attributed to the ease of on-site application, while eliminating the side effects such as tissue necrosis and nerve damage from puncturing soft tissues in the process of suturing. Most of the bioadhesives available in the market currently requires a stimuli such as heat or light for crosslinking. The bioadhesives that do not require activation have an inferior bonding strength, which limits its site of application. Biomimetic adhesives with micro-structured designs have a high and reversible adhesion strength, but they are complicated and expensive to fabricate. A recent development of a bioadhesive leverages on the covalent bonds formed between poly(vinyl alcohol) and boric acid to give a crosslinked structure with strong ester bonds that can undergo debonding in the presence of water. The synthesis of the gel is simple, and the resulting bioadhesive has a high adhesion strength with reversible bond that enhances the flexibility. This project aims to introduce the boronic ester bonds to the hydroxyl groups in diazirine-grafted polycaprolactone (CaproGlu), with the addition of boric acid, trimethyl borate, triethyl borate and tributyl borate. The crosslinking characteristics will be characterised with photorheometry, to obtain the viscosity, storage modulus, loss modulus, and stress-strain curve for different ratio of hydroxyl groups to borate ester sites. Successful crosslinking was observed between polycaprolactone polyol and CaproGlu, with all borate compounds, which was indicated by an increase in the viscosity from neat polycaprolactone polyol or CaproGlu. The highest visocity was observed at a low ratio of hydroxyl groups to borate ester sites. The crosslinked polycaprolactone gel softened when exposed to the atmosphere, possibly from the uptake of water from the environment. After photoactivation, CaproGlu with borate ester bonds showed a higher storage modulus across all borates and ratio tested. Amplitude sweep measurements also showed a higher maximum shear stress at the same shear strain. Further optimisation of the ratio between the hydroxyl groups in CaproGlu and borate ester sites may yield a higher shear strain for the sample, due to the reversibility of the boronic ester bonds.